2016
DOI: 10.1016/j.ijmyco.2016.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration between tuberculosis control programs and the action plan for tackling antimicrobial resistance: An opportunity in the Eastern Mediterranean Region

Abstract: Given the global commitment and potential availability of resources towards controlling AMR, collaboration between the two programs is discussed towards a more efficient use of resources in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore, another study highlighted recurring gaps in TB care across multiple EMR countries, primarily linked to restricted access to essential resources. 32 Collaborative efforts involving government agencies, non-governmental organizations, international partners, and civil society can help mobilize resources and support for TB prevention, surveillance, diagnosis, and treatment in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another study highlighted recurring gaps in TB care across multiple EMR countries, primarily linked to restricted access to essential resources. 32 Collaborative efforts involving government agencies, non-governmental organizations, international partners, and civil society can help mobilize resources and support for TB prevention, surveillance, diagnosis, and treatment in the country.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a comprehensive study conducted in Egypt found that a concerning 81% of Escherichia coli isolates displayed resistance to at least one antibiotic, with 62.5% showing resistance to multiple drugs [11]. To facilitate policy development and strategic planning for collaborative efforts, Hasan et al conducted a review of tuberculosis (TB) control and AMR programs in the EMR in 2016 [12]. This review identified gaps in TB care in several EMR countries, mainly due to limited resources.…”
Section: Review Amr In Eastern Mediterranean Countriesmentioning
confidence: 99%